Evaluation Models of MOOCs in China - Zheng, Qinhua; Li, Chen; Burgos, Daniel (Lecture Notes in Educational Technology, 2020)
Learning evaluation can not only be used to measure the learner’s learning achievement, but also can help teachers to understand the learning situation of the whole course. It is an indispensable part of MOOC learning. The purpose of this survey is to analyze the current situation of the evaluation of MOOCs and to compare the differences between different types of learning evaluation. For different types of curriculum evaluation methods for comparison, this study selected 356 course evaluation methods that are analyzed, according to the level of course category, class access permission, instruction mode, evaluation subject, and certificate of different course evaluation methods are compared and analyzed. The survey found that overall evaluation is at a lower level, course evaluation has not been designed well. Three most commonly used evaluation methods are the final exam, unit test, and participate in discussion; holistic course assessments tend to multiple features; evaluation body of whole course is more single, for the evaluation of machine; undergraduate and general curriculum evaluation are more comprehensive evaluation of the typical platform differences, evaluation methods of “good university online” platform are the most abundant, focusing more on line examination; the instruction model has a great influence on the evaluation methods; peer assessment courses pay more attention to process evaluation; a course offering two certificates have a more detailed evaluation design. According to the research findings, this paper suggests that our country MOOCS construction and application process need to realize the innovation of teaching idea renewal and learning evaluation, to explore the new mode of learning, to promote big data analysis of practical application, and to carry out personalized learning evaluation.
Capítulo del libro "Zheng Q., Chen L., Burgos D. (2018) The Development of MOOCs in China. Lecture Notes in Educational Technology. Springer, Singapore"
Keywords: Scopus(2); WOS(2)